An unusual case of pycnodysostosis. Issue 5 (May 1988) - Kumar, R; Misra, P K; Singhal, R
Abstract : A 6 year old boy with clinical and radiological features of pycnodysostosis is described. In addition to pycnodysostosis he had a myelophthisic type of anaemia suggesting an overlap with osteopetrosis.